PENERAPAN “ASAS TIDAK ADA EKSTRADISI UNTUK KEJAHATAN POLITIK” TERHADAP PENOLAKAN PERMINTAAN EKSTRADISI - Wibawa, Ketut Gede Sonny; Palguna, I Dewa Gede; Utari, Anak Agung Sri (Kertha Wicara : Journal Ilmu Hukum; Vol 1 No 01 (2012), 2012)
Political offense is the reason for rejecting the request for extradition of a country.However, in some cases turned out to still be done despite the extradition act as the basis ofan extradition request considered political crimes, or at least related to political crimes.Therefore, this paper will describe a nation justified in using “non extradition of politicalcriminal" against the rejection of the request for extradition if the crime is included inAttentate Clause, hotis humani generis and military crimes. This paper also describes theremedies that should be taken in the event of rejection of the request for extradition forpolitical crimes. So there is legal certainty and to avoid arbitrary action.Keywords: Extradition, Criminal Poli
Keywords: Extradition, Criminal Politics, Rejection, Request